Behavior of Composite Columns Subjected to Lateral Cyclic Loading - AL-Bdoor, Mazen (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2013)
ABSTRACT: Nonlinear 3-D finite element models were developed to investigate the cumulative damage of composite columns subjected to cyclic loading by comparing the effects of different levels of axial loads on the cyclic capacity of steel, reinforced concrete, and composite beam-columns. The beam-column specimens were modeled as fixed cantilever beam-columns with an axial load level of 10%, 15%, and 20% of their axial load capacity as well as cyclic loading similar to that suggested by Applied Technology Council (ATC) guidelines (ATC 1992 - ATC 24). The FEM output was then examined to determine the effect of different levels of axial loads on behavior of beam-columns under cyclic loading. Assessing whether the prototype elastic stiffness had changed, identifying the high stress and strain zones, and evaluating the effects of the level of axial load on stiffness, strength, and ductility of beam-column prototypes were facilitated. The finite element analysis results demonstrate that the encased composite beamcolumns reached the highest ductility among beam-columns specimens due to confinement effect of concrete. The results indicate that local buckling plays a crucial role in curvature ductility for the cyclic beam columns whereas extensive local buckling of steel section leads to significant reduction in stiffness and strength (softening damage). Moreover, the elastic flexural stiffness as well as ductility decreases significantly with an increase in the axial loads level. Keywords: Cyclic Capacity, Confinement Effect, Finite Element Method, Local Buckling, Ductility ………………………………………………………………………………………………………………………… ÖZ: Doğrusal olmayan üç boyutlu kompozit kolon modelleri sonlu elemanlar yöntemioluşturularak döngüsel yükler ve farklı eksenel yükler altında analiz edilmiş ve sonuçlar çelik ve betonarme kolon modelleri ile karşılaştırılmıştır. Kiriş-kolon modeli bir ucu tam ankastre diğer ucu serbest olacak şekilde modellenmiş (konsol kolon) ve ATC24 raporunda belirtildiği şekilde eksenel yük kapasitelerinin %10, %15 ve %20 değerlerine tekabül eden düşey yük ve döngüsel yatay yük uygulanarak çözümlenmiştir. Döngüsel yük uygulanan Kiriş-kolon sonlu elemanlar modellerinden elde edilen sonuçlar, eksenel yük oranı da dikkate alınarak incelenmiş ve farlı eksenel yük oranlarının döngüsel yatay yük kapasitesine olan etkisi değerlendirilmiştir. Bu çalışmada modellerin farklı eksenel yükler altında elastik rigitlik, yüksek gerilme ve yüksek birim şekil değiştirme bölgeleri, dayanım ve süneklik düzeyleri incelenmiş ve sonuçlar sunulmuştur. Sonlu elemanlar yöntemi uygulanarak elde edilen sonuçlardan kompozit kirişkolonun, betonun çelik profil etrafında oluşturduğı sargı etkisi nedeniyle, sünekliğinin diğerlerine göre daha yüksek olduğu görülmüştür. Ayrca sonuçlar göstermiştir ki döngüsel yüklerden dolayı oluşan bölgesel burkulma sünekliliği etkilediği, bu bağlamda çelik kiriş-kolonda görülen bölgesel burkulma nedeniyle bu elemanda ciddi bir rigitlik kayıbına neden olmuştur. Buna paralel olarak tüm modellerde eğilme rigitliğinde ve süneklikte eksenel yük artışı ile düşüş görülmüştür. Anahtar Kelimeler: Döngüsel yük kapasitesi, Sargı etkisi, Sonlu Elemanlar Yöntemi, Bölgesel Burkulma, Süneklik.
Master of Science in Civil Engineering. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Engineering, Dept. of Civil Engineering, 2013. Supervisor: Assist. Prof. Dr. Serhan Şensoy.
Keywords: Civil Engineering; Structural stability; Cyclic Capacity, Confinement Effect, Finite Element Method, Local Buckling, Ductility